Bone. Book 7, Ghost circles - Smith, Jeff, 1960 February 27-; Hamaker, Steve (New York : Graphix, 2008)
The Bone cousins, along with Gran'ma Ben and Thorn, struggle to reach the safety of the city of Atheia, on a journey that has become increasingly bleak with the release of the Lord of the Locusts.
Map on endpapers in hardcover.
Book Links (A.L.A.), May 2008.
3.0
3-6
GN380L
W
Keywords: Cousins -- Comic books, strips, etc -- Fiction; Cousins -- Juvenile fiction; Fantasy; Cartoons and comics; Fantasy fiction; Comic books, strips, etc; Graphic novels; Fantasy comic books, strips, etc; Graphic novels